Efektivitas Asap Cair Tandan Kosong Kelapa Sawit dalam Menekan Pertumbuhan Penyakit Layu Fusarium pada Tanaman Bawang Merah (Allium ascalonicum L.) - Ahmad Reza Syahputra Matondang; Ismed Setya Budi; Salamiah Salamiah (JURNAL PROTEKSI TANAMAN TROPIKA, 2022)
Shallots (Allium ascalonicum L.) are agricultural commodities that are goodly demanded by the community. Fusarium wilt caused by the fungus Fusarium oxysporum is a dominant problem in the cultivation of this plant. The way to control this disease is to use liquid smoke from empty oil palm fruit bunches. Conduct research in February-September 2021 at the Laboratory of the Plant Protection Study Program and Experimental Land, Faculty of Agriculture, University of Lambung Mangkurat Banjarbaru. Two-stage experiments (in vitro and in vivo) were carried out in this study, using a completely randomized design with five treatments (without treatment and liquid smoke with concentrations of 1, 2, 3%, and 4%). Fusarium oxysporum was injected in all treatments. The results of in vitro studies showed that giving as soon as possible with a concentration of 3% allows for inhibiting the growth of the fungus Fusarium oxysporum. in vivo showed that the application of 2 times a week is better than all treatments